Application of similarity solution to film cooling for flat plate - Osman, Kahar (2007)
In film cooling, cool air is bled from the compressor, ducted to one or more internal chambers of the turbine blades, and discharged through one or more cooling holes to form cooling jets. As a result of the cooling jets, convective heat transfer to the surface of the turbine blade can be reduced.